Phylogenetic Analysis and Pathogenicity Assessment of Two Strains of Avian Influenza Virus Subtype H9N2 Isolated from Migratory Birds: High Homology of Internal Genes with Human H10N8 Virus - Ye, Ge; Liang, Chai Hong; Hua, Deng Guo; Song, Lei Yong; Xiang, Yang Guo; Guang, Chen; Lan, Chen Hua; Ping, Hua Yu (Frontiers in Microbiology, 2016)
Two human-infecting avian influenza viruses (AIVs), H7N9 and H10N8, have emerged in China. This development further indicates that as an internal gene donor, the H9N2 subtype of AIVs may have an important role in the generation of new viruses with cross-species transmissibility and pathogenicity. H9N2 viruses that contain such internal genes are widely present in poultry but are rarely reported in migratory birds. In this study, two strains of the H9N2 virus were isolated from fecal samples of migratory birds in 2014 in China: one strain from Caizi Lake in Anhui Province and one from Chen Lake in Hubei Province. Nucleotide sequence analysis revealed the high homology of all six internal genes of these two strains with the internal genes of the human H10N8 virus in Jiangxi Province, as well as with the human H7N9 virus. Phylogenetic analysis indicated a possible origin of these two strains from poultry in South China. Both of the two viruses tested were able to replicate in the respiratory organs of infective mice without adaption, similar to both strains of H9N2 AIV from wild birds, suggesting their potential capacity to direct infecting mammals. Our findings indicate the existence of H9N2 viruses that contain internal genes that are highly homologous with the human H10N8 or H7N9 virus. Wild birds can contribute to the spread of the H9N2 virus, which contains a “harmful” internal gene complex, leading to gene rearrangement with other influenza viruses and to the generation of new pathogenic viruses. Therefore, strengthening AIV surveillance in wild birds can promote an understanding of the presence and prevalence of viruses and provide scientific evidence for the prevention and control of AIVs, including human-infecting AIVs.